The role of fibrin deposition in diabetic glomerulosclerosis: a light, electron and immunofluorescence microscopy study. Issue 8 (August 1972) - Farquhar, A.; MacDonald, Mary K.; Ireland, J. T.
Abstract : The possible role of fibrin deposition in the development of diabetic glomerulosclerosis has been investigated by light, immunofluorescence, and electron microscopy examination of renal tissue obtained by percutaneous biopsy from seven diabetic patients having minimal clinical evidence of renal involvement and at necropsy on nine diabetic patients. Although the biopsy specimens showed only early to moderate diffuse glomerulosclerosis without either nodular or exudative lesions, approximately 70% of glomeruli examined showed specific fluorescence for fibrinogen in a discontinuous linear pattern along the capillary basement membrane and diffusely in the mesangium. Moreover the immunofluorescence findings correlated well with the distribution patterns of material thought to be fibrin both in the light microscopy studies, by virtue of its staining properties, and by electron microscopy, because of periodicity, texture, and electron density. It is suggested that electron-dense granular deposits seen on electron microscopy may represent intermediate compounds in the fibrinogen to fibrin conversion, and that endothelial and mesangial trapping of fibrinogen or other macromolecules may initiate or accelerate mesangial enlargement, nodule formation, and irregularity of the basement membrane.